A retrospective study on the risk factors for retinopathy of prematurity in NICU of tertiary care hospital - K. C., Sundar; Meenakshi K., Devi; Patil, Aruna B. (International Journal of Contemporary Pediatrics, 2018)
Background: Retinopathy of prematurity (ROP) affects developing retinal vasculature in premature infants. The risk factors for ROP are prematurity, low birth weight, oxygenation, respiratory distress, infection and frequent blood transfusion. Identification of risk factors leading to ROP may help in planning preventive strategies. Methods: A retrospective analysis of records of preterm babies less than 34 weeks of gestation or birth weight less than 1750 grams and between 34 -36 weeks gestation or 1750-2000 grams birth weight associated with risk factors for ROP admitted to NICU of Kilpauk Medical college hospital from August 2015 to July 2016 were evaluated. Results: Out of a total of 166 babies who were screened for ROP, 37 babies were detected to have ROP (22.3 %). Of these 20 (54%) were female and 17 (46%) were male. The mean birth weight of babies with ROP identified in our study was 1480 grams. The mean gestational age of babies with ROP was 32 weeks. By logistic regression analysis for mode of oxygen therapy as a risk factor for ROP it was found that prongs alone showed the strong risk factor towards ROP which was statistically significant. Sepsis, transfusion and shock requiring inotropes individually and statistical significantly contributed to the risk of ROP. Conclusions: ROP was more common in babies <34 weeks. Sepsis, transfusion and shock requiring inotropes significantly contributed to the risk of ROP. Analysis of the mode of oxygen therapy showed that use of prongs significantly increased the risk of ROP.